A simulation study on angular and micro pattern effects in GEM detectors. (April 2016) - Kim, H.G.; Jamil, M.; Rhee, J.T.; Ahmad, Farzana; Jeon, Y.J.
Abstract: A useful approach for the enhancement of thermal neutrons detection has been reported here. This technique, based on the angular and micro pattern effects, has been developed and applied to the boron-coated ( 10 B) Gas Electron multiplier (GEM) detector. In the angular effect case, as a general rule, the detector device is turned at an angle which improves the device response per unit area of the detector. While for the latter case, a regular pattern in the form of micrometer deep grooves is fabricated onto the converter coating, consequently it enhances the capture probability of the detector. For the current study, both of these techniques using a 10 B-coated GEM detector have been simulated for low energy neutrons. For the evaluation of detector response thermal neutrons in the energy ranges from 25 meV to 100 meV were transported onto the detector surface. For this work, FLUKA MC code has been utilized. The output in both cases has been estimated as a function of incident thermal neutron energies. By employing both techniques, the angle and the micro pattern dependent efficiencies for 10 B-coated GEM detectors are presented, which indicate an improved efficiency response of the device. We anticipate that by using these modifications can lead a further forward step in the development and improvement of thermal neutron detection technology. Highlights: A useful approach for thermal neutrons detection is reported. The technique is based on the angular and micro pattern effects. Both of such methods were applied to GEM detectors. Simulation measurements were done via FLUKA MC code.